Development of Mobile-Based Crowdfunding Application - Rosalina Rosalina (Universitas Medan Area, 2023)
Charity is a personality trait shared by those who want to serve others without being asked. Charity has been practiced for a long time all over the world, particularly in Indonesia. Due to the rapid advancement of digital technology, a new route for charitable programs has emerged: crowdfunding. Anyone who wishes to generate funds or make a donation can use crowdfunding. Crowdfunding is a collaborative effort of individuals who network and pool their money, usually over the Internet, to support projects, to help friends, family, or even strangers. The most common barrier that fund seekers experience is publication challenges. Publication is significant in fundraising since it increases the quantity of money raised. This research therefore presents an Android mobile app application that allows users to fundraise for charity activities, make donations to charity projects, search for donation, evaluate them (by interacting with donees), choose one or more charitable program, and make an online payment. This research adopt the Rapid Application Development (RAD) approach to develop this mobile app’s system. The RAD approach enabled the development of the mobile app prototype to be completed quickly and enabled end users to test the mobile app to provide recommendations and make changes easily. Our research contribute to crowdfunding success factors related to publication barrier, user trust, privacy protection, perceived security, information quality.